A arquitetura de museus na obra do escritório Brasil arquitetura: os casos do museu do Pão, do Palacete das artes Rodin Bahia e do museu Cais do Sertão - Oliveira, Mylena Brasileiro de Lima (2019)
The research in question intends to analyze works of architecture and urbanism by the Brasil Arquitetura [Brazil Architecture] office focusing on the projects, methodology and principles of the partners — the architects Marcelo Ferraz and Francisco Fanucci. It will be done by means of studies focused on aspects of architecture and museology developed by them at the time of design, in which the Bread Museum, Palace of Arts Rodin Bahia and the Cais do Sertão Museum will be highlighted. To this end, a greater understanding of the constructive and creative processes used, as well as of the design procedures, parties, foundations and references in the design of such projects will be necessary, being the understanding of the social and cultural context of the training of these architects as well as of the places in which the objects of study are inserted.